Preliminary taxonomic survey and molecular documentation of jellyfish species (Cnidaria: Scyphozoa and Cubozoa) in Malaysia - Mohammed Rizman, I.; Farah Azwa, A.B.; Chong, V.C. (2016)
Scientific enqumes into jellyfish blooms and associated problems in Malaysia are often deterred by the lack of taxonomical and ecological studies. To date, only two scyphozoan jellyfish species have been documented from field surveysin Malaysian waters, whereas other four Malaysian scyphozoan and two cubozoan jellyfish species have been mentioned in toxicological studies, all of which their species identity were not verified. Thus,this study aimed to document and to resolve the identification of jellyfish in Malaysia using morphology and molecular DNA sequencing of COl, 16Sand ITS1 regions. Jellyfish specimens were collected from 2008 to 2010 in the Straits of Malacca, South-China Sea and the Sulu-SulawesiSea. Ten scyphozoan and two cubozoan species were recorded, which included eight species from the order Rhizostomeae (Rhizostomatidae, Lobonematidae, Mastigiidae, Catostylidae and Cepheidae), two species from Semaestomeae (Pelagiidae and Cyaneidae) and two species from class Cubozoa; one from order Carybdeida (family Carukiidae) and another from order Chirodropida (family Chiropsalmidae). TheCOl phylogenetic tree of Cubozoa and Scyphozoa species from the Atlantic and Pacific region showed distinct clustering of sixMalaysian jellyfish species. However, most of the deeper divergences and relationships between the families were unresolved, which were also observed in the 16Sand ITS1 phylogenetic trees. The Malaysian edible species Lobonemoides robustus, Rhopilema hispidum and Rhopilema esculentum were proven to belong to Rhizostomeae, whereas other scyphozoans showed phylogenetic affinities to Semaestomeae and Kolpophorae. Chrysaora and Cyan eo appeared non -monophyletic, however their paraphyly was not confirmed. Although this study has provided much needed baseline information on the barcoding of Malaysian jellyfish species, there isstilla general lack of jellyfish sequences in GenBank to facilitate better species confirmation.